Effect of Carbon Sources on the Biomass Build-Up and Degradation of Rubber Processing Industry Effluent - Girish, K. (International Journal of Applied Sciences and Biotechnology, 2014)
Rubber processing industry effluent represents a serious environmental pollution problem especially for underground and surface water. Wastewater collected from rubber processing industry was characterized for their pollution characteristics. Analysis showed that the biological oxygen demand (BOD), chemical oxygen demand (COD), total dissolved solids (TDS), total suspended solids (TSS), total solids (TS), ammonia and phosphate were high when compared to effluent discharge standard for industrial wastewater. Four bacterial species were isolated from the wastes and were identified as Arthrobacter sp., Bacillus sp., Lactobacillus sp., and Pseudomonas sp. A bacterial consortium was constituted by mixing proportionately these four bacteria and used in effluent aerobic biotreatment. Complex carbon sources such as bagasse, corn-cob, rice straw, wheat bran, molasses, corn steep liquor, were screened for their effect on growth of the consortium constituted. Highest biomass production was in molasses followed by rice straw hydrolysate, wheat bran hydrolysate and bagasse hydrolysate. However, the inoculum grown on rice straw and wheat bran hydrolysate caused maximum degradation in terms of reduction in various parameters such as BOD, COD, TDS, TSS, NH4+ and PO43, about 70 to 80% reduction was observed. From the results of the present study it could be inferred that the constituted consortium could effectively be used for the treatment of effluents from rubber processing industry and rice straw and wheat bran hydrolysate could be used for mass production of effective consortium. DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11532Int J Appl Sci Biotechnol, Vol. 2(4): 579-584